2004
DOI: 10.1212/wnl.62.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic studies in hereditary spastic paraplegia with thin corpus callosum

Abstract: HSP-TCC is common in Italy. The phenotype is fairly homogeneous and is associated with impaired cognition. There are at least two loci for HSP-TCC, one of which is on chromosome 15q13-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
68
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 17 publications
20
68
0
Order By: Relevance
“…The clinical presentation and the MRI features in such cases did not grossly differ from patients having both alleles mutated. These findings reinforce previous notions on genetic heterogeneity in ARHSP-TCC (Casali et al 2004;Boukhris et al 2008a). Although the presence of non-conventional variants remains possible, mutations in other genes are also to be expected.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The clinical presentation and the MRI features in such cases did not grossly differ from patients having both alleles mutated. These findings reinforce previous notions on genetic heterogeneity in ARHSP-TCC (Casali et al 2004;Boukhris et al 2008a). Although the presence of non-conventional variants remains possible, mutations in other genes are also to be expected.…”
Section: Discussionsupporting
confidence: 90%
“…Since the initial reports linking Mediterranean and Asian ARHSP-TCC families to the SPG11 locus on chromosome 15q (Martinez-Murillo et al 1999;Shibasaki et al 2000), several groups, including our teams, proved that this phenotype has a worldwide distribution (Casali et al 2004;Lossos et al 2006;Olmez et al 2006;França et al 2007;Stevanin et al 2007Stevanin et al , 2008a and that it is particularly prevalent in the Mediterranean basin (Casali et al 2004;Stevanin et al 2006). More recently, we showed that ARHSP-TCC at this locus is associated with mutations in SPG11/KIAA1840 (MIM# 610844), a gene with an open reading frame of 7,787 nucleotides that comprises 40 exons and which spans a genomic region of approximately 100 Kb .…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Disease causing variants in SPG11 (KIAA1840) (OMIM phenotype #604360) constitute the most frequent cause of TCCassociated HSP (41-77%) and up to for 10-20% of all AR HSP, particularly in the Mediterranean basin. 6,10,[12][13][14][15][16] Next-generation sequencing aided in the identification of many rare HSP genes. 1,17 TFG/SPG57 stands as an example of this genetic surge.…”
Section: Introductionmentioning
confidence: 99%